General overview to treatment of strong ion (metabolic) acidosis in neonatal calves with diarrhea - Ismail Sen; Peter D. Constable (Eurasian Journal of Veterinary Sciences)
Diarrhea in neonatal calves is due to one or more causes. Strong ion (metabolic) acidosis is common in diarrheic calves. Clinical signs associated with metabolic acidosis are vague and nonspecific. However, the calf's age can be used to predict the severity of metabolic acidosis, because one weak old diarrheic calves are less acidemic than older calves despite they have similar clinical signs. Moreover, the suckling reflex is closely associated with base excess parameters. One of the most important factors for decreasing mortality rates associated with diarrhea in calves is parenteral and oral administration of appropriately formulated electrolyte solutions. Inclusion of an alkalinizing agent is required to correct systemic metabolic acidosis. Bicarbonatecontaining fluids are more effective at rapidly correcting severe acidemia, since bicarbonate reacts directly with H+ ions. Lactated Ringers solution or Acetated Ringers solutions can be used to correct mild to moderate acidosis.